Konsep Skematik Desain pada Perencanaan dan Perancangan Gedung Pameran Seni Kontemporer di Ubud, Gianyar - I Wayan Yoga Astra; I Nyoman Warnata; I Wayan Parwata (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Ubud, Gianyar Bali, has a rapid development in the field of art. The emerging arts are contemporary art, contemporary art, contemporary fine art, contemporary painting, to contemporary installation art. The rapid development of art and the interest of the Balinese people in art are not balanced with the art facilities in Bali. Actually, in terms of the potential of contemporary art, Bali is the most superior in Indonesia. But because they do not have the space to provide facilities to them (artists), then finally many exhibit outside Bali and even abroad, therefore, it is time for Bali to prepare the right space for balinese contemporary artists.The study begins with learning the meaning and basics of the Art Exhibition Building, the understanding of contemporary art itself, standards regarding the layout of the art in the Art Exhibition Building, comparative study of several Art Galleries in Bali and Galleries – Contemporary Art Galleries outside the City of Bali.